2012
DOI: 10.1016/j.chemphyslip.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Chemical–physical characterization of isolated plant cuticles subjected to low-dose γ-irradiation

Abstract: Isolated tomato fruit cuticles were subjected to low dose (80 Gy) -irradiation, as a potential methodology to prevent harvested fruit and vegetables spoilage. Both irradiated and non-irradiated samples have been morphologically and chemically characterized by Scanning Electron (SEM), Atomic Force (AFM), Attenuated Total Reflectance Fourier Transform Infrared (ATR-FTIR) and X-ray Photoelectron (XPS) spectroscopies. Additionally, electrochemical measurements comprising membrane potential and diffusive permeabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 24 publications
(23 reference statements)
0
9
0
Order By: Relevance
“… ATR-FTIR spectra of cutin (adapted from España et al, 2014, with permission of John Wiley and Sons), waxes (adapted from Heredia-Guerrero et al, 2012, with permission of Elsevier), and polysaccharides (adapted from López-Casado et al, 2007) of isolated tomato fruit cuticle .…”
Section: Characterization Of Plant Cuticles and Cuticle Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“… ATR-FTIR spectra of cutin (adapted from España et al, 2014, with permission of John Wiley and Sons), waxes (adapted from Heredia-Guerrero et al, 2012, with permission of Elsevier), and polysaccharides (adapted from López-Casado et al, 2007) of isolated tomato fruit cuticle .…”
Section: Characterization Of Plant Cuticles and Cuticle Componentsmentioning
confidence: 99%
“…This ratio has been used for qualitative comparisons by several authors (even in isolated plant cuticles) and calculated in different forms (Benítez et al, 2004b; Chefetz, 2007; Girard et al, 2012; Heredia-Guerrero et al, 2012; España et al, 2014). We recommend the ratio of intensities ν (C=O)/ν a (CH 2 ) and the denomination of “esterification index.” Thus, values of the “esterification index” are directly related to the cross-linking of cutin.…”
Section: Characterization Of Plant Cuticles and Cuticle Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the distance between the peaks at 730 and 720 cm −1 and between 1460 and 1455 cm −1 increased. Splitting, shifting to lower wavenumbers and increasing of peak intensity are related to the increase of the crystallization degree (Borchman et al 2011;Brubach et al 2007;Heredia-Guerrero et al 2012;Srivastava et al 1993;Ungar and Masic 1985). The increase in intensity of the peak at *720 cm −1 is related to the increase of the amount of alkyl chains, not necessarily assembled in an organized way (e.g.…”
Section: Resultsmentioning
confidence: 96%
“…However, studies of several cutin mutants have revealed characteristic changes in the morphology of the petal nanoridges (Panikashvili et al, 2010(Panikashvili et al, , 2011Bessire et al, 2011;Shi et al, 2011), and mutants with a reduction of .95% of the amount of 10,16-dihydroxy hexadecanoic acid (cyp77A6, gpat6, and dcr) do not have petal nanoridges (Li-Beisson et al, 2009;Panikashvili et al, 2009). In addition, initial studies aimed at correlating the structure and function of cuticles, including an assessment of the physicochemical properties, have exploited micrometerthick cuticles, such as those of tomato fruits (Heredia, 2003;López-Casado et al, 2007;Heredia-Guerrero et al, 2012;España et al, 2014).…”
mentioning
confidence: 99%